A Simple Algorithm for Drawing Apportionment Diagrams. (1st January 2023) - McCune, David
Abstract: This article gives an algorithm that will build an apportionment diagram for any apportionment method when there are three states. We then provide several images that are produced by the algorithm and discuss what these images can reveal about the given apportionment method.